The Role of Religiosity Dimension on Muslim Women’s Behavior toward Fashion: Study Case of Indonesia - Meita Larasati; Ani Silvia; Zulpahmi Zulpahmi; Sunarta Sunarta (Proceedings of AICS - Social Sciences, 2018)
This study finds empirical evidence of a significant negative relationship between religiosity dimension and Muslim women’s behavior toward fashion in Indonesia. This study uses a survey method utilizing questionnaires that were distributed to some universities in Jakarta and West Java. Using a purposive sampling technique, the collected data are 165 questionnaires. The measurement variables of religiosity dimensions in this study are adapted from Glock (1972) and consist of five different dimensions including ideology, intellectual, ritualistic, experiential, and consequential. The measurement of Muslim women’s behavior toward fashion is adapted from Farrag and Hassan (2015). All collected questionnaires are analyzed using the Pearson correlation test. The relationship is around 15% - 29%. Ideological and ritualistic dimensions have a strong negative correlation (29%), consequential (28%), intellectual (23%) and experiential (15%).Keywords: religiosity, religiosity dimensions, Muslim women’s behavior, fashion.